Mempertanyakan Konsep Al-Naskh dalam Alquran - Rahman, Andi (Jurnal Studi Al-Qur'an, 2009)
Alquran denying the contradiction among its verses. However, we realize that there are some contradictive verses of the Quran in terms of the zahir. To understand the verses, the majority of ulama, use many method, including the naskh. Some ulama say that the naskh concept in Islam to understand Alquran is not a debatable fact. But this article tries to argue against it.